Biological properties of sodium alkyl methyl ester sulfonate/alkyltrimethylammonium bromide surfactant mixtures - Chuah, C.H.; Wong, S.P.; Lim, W.H.; Cheng, S.F. (Elsevier, 2012)
Quaternary ammonium compounds (QACs) are commonly used as disinfectant in medical care, food industry, detergents and glue industries. This is due to a small concentration of QACs is sufficient to inhibit the growth of various bacteria strains. In this work, the inhibitive power of cationic surfactants,alkyltrimethylammonium bromide (CnTAB) in the presence of anionic surfactants, sodium alkyl methyl ester α-sulfonate (CnMES) was studied. The growth inhibition test with gram-positive (Staphylococcusaureus) and gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacteria were used to determine the toxicity of single and mixed surfactants. Results from this work showed that certain mixed surfactants have lower minimum inhibition concentration (MIC) as compared to the single CnTAB surfactants. Besides that, it was also found that alkyl chain length and the mixing ratios of the surfactants play a significant role in determining the mixture inhibitive power.